CLINICAL STUDY OF INDIGENOUS DRUGS - PATHADI KWATHA IN THE MANAGEMENT OF ARSHA (HEMORRHOIDS) (AYUSHDHARA, 2016)
One of the fast developing branch of Surgery, gained momentum among the various branches of surgery because of manifold increase in incidence of ano-rectal diseases in population as compared to other diseases. As per Ayurveda today's dietary habits are totally controversial, that is, it is totally against the 'Ahar - vidhi visheshayatane'. The ultimate result of this is altered bowel habits which finally results in constipation which may lead to Arsha i.e. Hemorrhoids.Acharya Charka recognizes "Mandagni" as causative factor and further elaborated and emphasized this point saying that Arsha (Haemorrhoids), Atisara (Diarrhoea) and Grahani (Spure) are sometimes causative to each other resulting from Mandagni i.e. weak digestive fire.As per Sushruta the causes leading to variation of Dosha including excessive and erroneous dietetic indulgence, posture which create pressure on the anal region, sexual indulgence and suppression of normal urge of micturation, defecation etc. leads to developing "Arsha".The results of this clinical study, itself are sufficient to comment that 'Pathadi Kwatha' has definite effective role in the management of all types of Arsha in early stage. The Statistical Analysis reveals that In management of all types of Arsha in early stage the Pathadi Kwatha is effective. The conclusion of this clinical study 'Pathadi Kwatha' has definite effective role in the management of all types of Arsha in early stage.